Electrical Energy Steam Boiler Heat Loss Analysis in Japfa Comfeed Indonesia Tbk, Unit of Sidoarjo - Joseph Priyandana; Jamaaluddin Jamaaluddin (Widyagama University of Malang, 2018)
In the animal feed industry, steam is used in pellet making machines. In this process, steam from the boiler is distributed to the pellet mill through the pipe. The purpose of this study is to observe the waste of electricity costs of operating a boiler by calculating heat loss in a distribution pipe. The method of assessing heat loss is done by calculating losses caused by heat loss in the boiler distribution. Then make a calculation application model based on the data obtained. From the data analyzed, the amount of heat lost in the non-insulating distribution pipe is 0.766 kJ/s with a loss of Rp 5.628,600 operating costs per month compared to heat loss in an isolated pipe condition of 0.047 kJ/s with losses which cost slightly more than Rp 368 190 / month. This heat loss calculation process is made on an android application by entering the calculation formula on the program and the data that has been obtained.